ECHO answers small-farm need - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A newsletter sharing information about what does and does not work on the small, third world farm is published by ECHO (Educational Concerns for Hunger Organization), a Christian, non-profit group based in Florida, USA. ECHO exists to provide...